La física de la fuerza impresa y sus implicaciones para la enseñanza de la mecánica - Peduzzi, L.O.Q.; Zylbersztajn, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
When examining learners’ understanding of questions involving the movement of projectiles one notices, in general, that their common sense is far away from making any reference to aristotelianantiperistasis. Thecauses fora ‘violent’ or forced movement are seen as located in the body itself, following from the projectile-projector interaction. This is essentially the concept of impressed force, introduced by astronomer Hipparcus (second century BC) and adopted by Philoponus (sixth century), among others. The notion of impressed force has an interesting historical development. It may have been a reference for the establishment of the impetus theory by Buridan in the fourteenth century, and was part of the debate that took place from the twelfth century onwards about the possible movement of a projectile in the void. This work explores historically this concept, making use of it in problem situations that are both well familiar to the students and relevant for the development of mechanics. From the point of view of teaching that takes into consideration the learners’ ideas, this theme has great didactic potential for the development of strategies to help the reformulation of their conceptions, turning them more consistent with what is accepted as scientific today.